2021
DOI: 10.1186/s12882-021-02547-z
|View full text |Cite
|
Sign up to set email alerts
|

Higher one-year achievement rate of serum phosphate associated with lower cardiovascular mortality in hemodialysis patients

Abstract: Background Estimation of phosphate load in hemodialysis patients is always controversial in clinical practice. The aim of this study was to verify individual achievement rate of serum phosphate as the evaluation of phosphate load through investigating its impact on cardiovascular mortality in hemodialysis patients. Methods This was a single-center, retrospective cohort study. A total of 251 maintenance hemodialysis patients were enrolled. The indiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Therefore, by analyzing the regulation of phosphorus metabolism networks and clarifying the compensatory mechanism and underlying causes of phosphorus overload under different conditions, we can control phosphorus overload in a targeted manner. We have also demonstrated that, in hemodialysis patients, the bone disease still contributes the most to phosphorus burdens, followed by dietary factors [94], suggesting that actions may be taken on the basis of bone disease markers. However, in hemodialysis (HD) patients with substantial residual kidney function (RKF), RKF was the only independent predictor of serum phosphorus levels [102].…”
Section: The Path Forwardmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, by analyzing the regulation of phosphorus metabolism networks and clarifying the compensatory mechanism and underlying causes of phosphorus overload under different conditions, we can control phosphorus overload in a targeted manner. We have also demonstrated that, in hemodialysis patients, the bone disease still contributes the most to phosphorus burdens, followed by dietary factors [94], suggesting that actions may be taken on the basis of bone disease markers. However, in hemodialysis (HD) patients with substantial residual kidney function (RKF), RKF was the only independent predictor of serum phosphorus levels [102].…”
Section: The Path Forwardmentioning
confidence: 69%
“…Chronically elevated serum phosphorus levels, even in the normal range, are likely an expression of a prolonged exposure to phosphorus overload. If serum phosphorus was regularly followed in hemodialysis patients, the one-year serum phosphorus achievement rate (defined as the number of tests within the target range [2.5-4.5 mg/dL] divided by the total number of tests given throughout a year) may be a better indicator than one-time phosphorus or averaged phosphorus levels [94]. Keeping the one-year achievement rate of serum phosphorus higher than 50% provides significant clinical benefits in reducing cardiovascular mortality [94].…”
Section: Early Markers Of Phosphorus Overloadmentioning
confidence: 99%